When is a Defence Review Not a Defence Review?: The Impact of the National Security Capability Review and Modernising Defence Programme. Issue 2 (23rd February 2019) - Curtis, Andrew
Abstract : This article examines the impact of the National Security Capability Review (NSCR) and Modernising Defence Programme (MDP) on the UK's existing strategic defence and security process. Andrew Curtis specifically assesses the appropriateness of conducting the NSCR and MDP discretely from the quinquennial Strategic Defence and Security Review process, and the consequences of undertaking them for defence reviews in the future.